The Development of the Middle Assyrian Provinces - Llop-Raduà, Jaume (Altorientalische Forschungen, 2012)
In this paper, a description of the Middle Assyrian provincial system arranged geographically, beginning with the heartland and continuing to the west, north and east, and chronologically, from the 13 th to the 11 th centuries BC, is undertaken. The expansion of this system was directly linked to the territorial expansion of the Middle Assyrian kingdom. Whereas most of the provinces can be followed from the 13 th to the 11 th century, some of them appear only for a shorter, limited period of time. According to present evidence, it seems that the term ḫalzu (district) was substituted by the concept pāḫutu (province) at the end of the reign of Tukultī-Ninurta I (1233–1197 BC) or shortly after his death.